Global and regional trends in the burden of surgically confirmed endometriosis from 1990 to 2021 - Ruijie Li; Ling Zhang; Yi Liu (Reproductive Biology and Endocrinology)
Abstract Background endometriosis as a common gynecologic finding significantly affects the quality of life of many women. An accurate understanding of the epidemiological characteristics of endometriosis is essential for disease control and prevention. We aimed to use the latest data from the Global Burden of Disease (GBD) 2021 to comprehensively analyze the various epidemiological indicators of surgically confirmed endometriosis and their changing trends to better measure the disease burden and help improve health management. Methods We delineated incidence, prevalence, and years lived with disability (YLDs) of surgically confirmed endometriosis at the global, regional, and national levels. The estimated annual percentage change (EAPC) was calculated to assess temporal trends in the age-standardized rate (ASR). In addition, we used joinpoint regression models to describe local trends in these indicators, assessed the correlation between disease burden and Socio-demographic index (SDI) levels, and used decomposition analysis to quantitatively analyze the driving factors leading to changes in disease burden. Results Globally, the age-standardized rate of incidence, prevalence, and YLDs of surgically confirmed endometriosis all showed a decreasing trend from 1990 to 2021. The burden of surgically confirmed endometriosis is mainly concentrated in women aged 20–30 years and declines with increasing SDI levels. The results of the decomposition analysis indicated that population growth is the main driving factor for the upward in the number of incidence, prevalence, and YLDs cases of endometriosis worldwide. Conclusions The overall burden of endometriosis has decreased globally from 1990 to 2021, but there are regional disparities. Managing this condition remains a major challenge, and more refined policies and interventions are needed to effectively address the burden of endometriosis.